Variations in the composition and biochemical attributes of Eucalyptus camaldulensis L. leaves essential oil as function of drying methods - Saleem, Misbah; Shaheen, Muhammad Ashraf; Qadir, Rahman; Saba, Iram; Rehman, Muhammad Misbah ur; Paracha, Rizwan Nasir; Ahmad, Nazir; Riaz, Muhammad; Anwar, Farooq (Har Krishan Bhalla and Sons, 2023)
The current study focuses on the chemical composition and biological properties of the hydro-distilled essential oil from Eucalyptus camaldulensis leaves, including its antibacterial, antioxidant, and anti-inflammatory properties. Three distinct drying techniques (sun drying, shade drying, and oven drying) were used to dry the plant leaves. The yield of essential oils from E. camaldulensis leaves (ELEOs) ranged from 1.0% (shade-dried sample) to 2.25% (sun-dried sample). The strongest antibacterial activity against Bacillus subtilis was seen in the essential oil from shade-dried leaves, which also had notable antioxidant and anti-inflammatory potential. The shade-dried variant, which was followed by the sun-dried and oven-dried variants, had the highest total phenolic contents (TPC), total flavonoid contents (TFC), and DPPH scavenging potential. These values were 54.07, 38.95, 16.86 (GAE mg/100g for TPC), 66.43, 29.09, 3.76 (CE mg/100g for TFC), and 66.58, 54.56, 24. 25 (IC50 μg/mL for DPPH scavenging). The shade-dried ELEOs, among others, with paw diameters of 0.739, 1.133, and 1.143 mm at 0, 30, and 60 min, respectively, showed the strongest inhibition of anti-inflammatory activity. According to GC-MS analysis, 1,8-cineole (28.08-42.70%), terpinol (11.19-19.28%), terpen-4-ol (9.74-12.33%), and β-pinene (7.89-9.51%) were the prominent components found in the evaluated ELEOs, followed by p-cymene (4.96-5.92%). The volatile profile and biological activity of ELEOs show wide variations in this study depending on the drying technique. Overall, these findings encourage peel samples to be dried at room temperature in order to gain maximal nutritional and nutraceutical benefits of this under-utilized agro-waste.